Syntactical Marker -Nya In Indonesian - I Nyoman Sedeng (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2015)
This study discusses the syntactic marker -nya in Indonesian, and aims at finding the answers to the three research questions; (i) what hosts can be appended by -nya,(ii)what syntactic functions can be filled by -nya, and (iii) what is the meaning of -nyacontextually. The data to support the analysis was collected from the source with the help of a data collection tool [antconc3.2.1w window2007]. Two theories are relevant to the discussion of -nya, namely; morphosyntactic theory that searched the occurrence of -nya in a text and discourse theory to discover the meaning of -nya contextually.The result of analysis showed three occurrence of -nya; pronoun clitics, determiner, and as adverbial formation. As a core argument -nya can be attached to the nasal verbs, passive verbs, zero intransitive verbs, and category of nouns, prepositions, and reflexive pronouns. As adverbial formation -nya is attached to the adjective, bound root, and is combined with se- to form confix se-baik-nya. As pronoun, -nya can serve as; Grammatical Subjects and Objects, Possessive determiner, Oblique Agent, Reflexive pronoun. As determiner it is always attached to the noun, forming nouns from verbs, and as an adverbial it can serve as an adjunct, conjunct, and disjunct. The meaning of -nya with pronominal category should be traced in the text and always refers to the third person singular.Â Keywords: syntactic markers, pronouns, argument, adverbial, discourse